Neurocorrection. On the use of neurodevices for criminals - Fuselli, Stefano (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2021)
The possibility of using neurodevices to treat criminal offenders, as a means of voluntary diversion to avoid incarceration, has become a widely discussed topic in the last decade. A widely debated issue concerns the right to control or alter the neurological patterns of criminal offenders, provided that punishing implies limiting one’s autonomy also without their consent. On the one hand, mandatory neurointervention is not only meant to be a lesser evil than incarceration, but it is even supposed to be advantageous for criminals because it can allow to restore their decisional autonomy by inhibiting their criminal impulses. On the other hand, mandatory neurointevention is rejected because it is considered to inflict significant harm on an offender, which goes far beyond the limits of criminal punishment. Some scholars have argued that the issues at stake call for a resemantisation of notions like mental integrity, freedom of thought, and cognitive liberty. My aim is to show that this resemantisation cannot preserve the specificity of legal categories if it is not set free from the naturalistic background, which underpins the uses of neurocorrection tools, in order to preserve the specificity of legal categories. For this purpose, I will analyse, in particular, some arguments offered by J.C. Bublitz.